The Role Of Restaurant Tax And Contribution To Regional Income In Gorontalo City - Finnantia Monicha Rikardin; Merindah Dwi Nabilqodarsa; Galih Wicaksono; Mu’min Al - Mukhlishin (ARBITRASE: Journal of Economics and Accounting, 2022)
Restaurant tax is one part of the regional tax that contributes a significant amount to local revenue (PAD). The purpose of this study was to determine the effectiveness and contribution of restaurant tax revenue to Gorontalo City PAD. The method used in this study is quantitative descriptive, namely measuring the level of effectiveness and contribution of Restaurant Tax to Gorontalo City's PAD from 2019 to 2021. Data collection was carried out secondaryly via the yanjak.gorontalokota.go.id page. From the research conducted, the results show that restaurant taxes are in the effective category, while the contribution to Gorontalo City's PAD is still lacking, so there is a need for an appropriate strategy to optimize restaurant tax revenue.